STUDI OBJEK WISATA CANDI MUARA TAKUS DI KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Saputri, Andesta Loni (Pendidikan Geografi, 2014)
This study aims to obtain data or information, discuss and analyze studies Barelang temple attractions namely (1) Condition of Transportation, (2) accommodation, (3) Promotion of attraction Barelang temple in District XIII Koto Kampar Kampar district. Jennies Adela qualitative research, research that aims to understand the phenomenon of research subjects. The technique of taking informants by means purposife sampling (designation), which became the subject of research in the study is, the Department of Tourism, Supervisor / Manager, Village and Temple Visitor attractions Barelang. When the study was conducted from August 13 to 13 October 2014 Data was collected through observation, interviews, and documentation. The results of the field study as follows: transport conditions to the temple attraction Barelang inadequate, yet adequate accommodation and promotion of this attraction is good.